The Influence of Work Motivation and Compensation on the Performance of Civil Servants in the Payung Sekaki District Office, Pekanbaru City - Ardiles; Kiki Joesyiana; Desi Susanti; Setiawati (PT FORMOSA CENDEKIA GLOBAL, 2023)
The basic capital to be able to show performance is mastery of expertise (competence) which includes: technical competence, namely mastery of certain scientific fields such as technology, law, economics, and others. Managerial competence, this is associated with a person's ability in the field of leadership to empower all available resources. Behavioral competence, in this case involves ethics, emotional mastery, motivation and the level of one's wisdom. So motivation as a measure of strength that can encourage someone to behave that can take action internally and externally positively or negatively to provide direction that depends on the strength possessed by the leader. Based on the results of the coefficient of determination (Adjusted R Square) of 0.512 or 51.6%, this means that 51.6% of the employee performance variables can be explained by work motivation and compensation variables. While the remaining 48.4% by other variables not examined. It can be concluded that this study shows that motivation and compensation have an effect on employee performance at the Payung Sekaki Subdistrict Office of Pekanbaru City.